Challenging diagnosis of renal failure associated with severe neurological symptoms in a patient with mixed connective tissue disease. Issue 1 (February 2023) - Gros, Clothilde; Fogel, Olivier; Boudhabhay, Idris; Debiais, Charlotte; Duong Van Huyen, Jean-Paul; Hummel, Aurélie; Allanore, Yannick; Avouac, Jérôme
We report the case of a patient followed for a mixed connective tissue disease with signs of systemic sclerosis and systemic lupus, who presented an acute renal failure with severe neurological symptoms (confusion, obnubilation) and hypertension. The distinction between scleroderma renal crisis and lupus nephritis was challenging and hence, the decision to use or not high dose of corticosteroids. Kidney biopsy was of major importance for the diagnosis and therapeutic strategy. The diagnosis of neurological symptoms was also made difficult given the clinical presentation and the results of imaging. Neurolupus, malignant hypertension, or posterior reversible encephalopathy syndrome were the evoked diagnosis.